2012
DOI: 10.1111/j.1755-3768.2011.02305.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of choroidal perfusion and thickness following systemic sildenafil (Viagra®)

Abstract: Objective To demonstrate anatomic and physiologic changes in the human choroid following systemic sildenafil citrate (ViagraR) using enhanced depth imaging spectral domain-optical coherence tomography (EDI-OCT) and swept-scan high frequency digital ultrasound. Methods Seven healthy male subjects (mean age 32.7 years) were evaluated at baseline and two hours after ingesting 50 mg of sildenafil. Swept-scan high frequency digital ultrasound and EDI-OCT were utilized to measure choroidal perfusion and thickness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 30 publications
5
63
1
2
Order By: Relevance
“…In high myopia, retinal dystrophy, and age-related choroidal atrophy, the choroid was reported to have decreased thickness, whereas increased choroidal thickness was reported in central serous chorioretinopathy and Vogt-Koyanagi-Harada disease. [15][16][17][18][19] Also, there is recent data on the hemodynamic effect of chemicals-sildenafil and nicotine-on choroid, obtained by OCT. 20,21 In our population of 160 patients aged 4-23 years, we found a mean SFCT of 308 mm with substantial variation between individuals, which was consistent with previous studies in adults. 4,22 Recent studies examining in vivo choroidal thickness with OCT in children have reported mean SFCT values of 348 mm (in 48 Korean children aged 4-10 years), 9 330 mm (in 194 children aged 4-12 years), 10 and 342 mm (in 174 children aged 3.5-15 years).…”
Section: Discussionsupporting
confidence: 79%
“…In high myopia, retinal dystrophy, and age-related choroidal atrophy, the choroid was reported to have decreased thickness, whereas increased choroidal thickness was reported in central serous chorioretinopathy and Vogt-Koyanagi-Harada disease. [15][16][17][18][19] Also, there is recent data on the hemodynamic effect of chemicals-sildenafil and nicotine-on choroid, obtained by OCT. 20,21 In our population of 160 patients aged 4-23 years, we found a mean SFCT of 308 mm with substantial variation between individuals, which was consistent with previous studies in adults. 4,22 Recent studies examining in vivo choroidal thickness with OCT in children have reported mean SFCT values of 348 mm (in 48 Korean children aged 4-10 years), 9 330 mm (in 194 children aged 4-12 years), 10 and 342 mm (in 174 children aged 3.5-15 years).…”
Section: Discussionsupporting
confidence: 79%
“…20 In contrast, it has been reported that sildenafil citrate increases choroidal thickness owing to a vasodilator effect on choroidal circulation. 21 In another recent study, subfoveal choroidal thickness, measured by enhanced depth imaging OCT (EDI-OCT), was not found to be significantly correlated with choroidal blood flow in young healthy eyes. 22 The authors speculated and suggested that further prospective studies are required to determine the changes in choroidal thickness during the stimulation that can cause choroidal circulation changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, in two different studies, the authors reported that sildenafil citrate increases choroidal thickness because of the vasodilatory effect of sildenafil citrate on the choroidal circulation. 25,26 Histopathological studies showed that PEX accumulations in the ocular and peribulbar tissues have been detected not only in affected eyes, but also clinically unaffected eyes and therefore it was stated that the socalled unilateral PEX syndrome is clinically asymmetric rather than truly unilateral. 27 Our study showed that the eyes of patients in the bilateral PEX group (group 3) and the affected eyes of the patients in the unilateral PEX group displayed choroidal thicknesses that were thinner than those of the eyes of normal subjects (group 4) and the unaffected eyes of the patients in the unilateral PEX group (group 2).…”
Section: Discussionmentioning
confidence: 99%